Differences in motivation of health care professionals in public and private health care centers - Babić, Lepa; Kordić, Boris; Babić, Jovana (The European Journal of Applied Economics, 2014)
It is very important to achieve client satisfaction in the health care sector, which is why the issue of motivation of health care professionals is always an interesting topic to explore. Having in mind the current situation in the private health care sector in Serbia, we have decided to examine the differences in satisfaction of motivational needs in health care professionals, with an emphasis on differences between health care professionals working in public and private health care centres. We have used Maslow and Herzberg’s motivation theories when designing the appropriate questionnaire. The results obtained have revealed differences between subsamples. Health care professionals working in the private sector are more satisfied with their salaries, working conditions, job certainty and opportunities for professional development.